“Estimación del índice de mérito total del programa de mejoramiento genético sostenible de bovinos de leche de La Comunidad Cumbijín Parroquia San Miguel” - Lema Coro, Luis Felipe (2023)
The present investigation had the purpose of estimating the total merit index in dairy cattle of the Cumbijín community belonging to the San Miguel parish, using the reference method for the assignment and prediction of the genetic value in animals, called the BLUP system, knowing that dairy production in Ecuador contributes to 1% of GDP and sustains 1.2 million people, but it is inefficient since producers lack technical knowledge, implementation of technology such as genetic improvement, lack of records and evaluation of cows and bulls in cattle herds. In the Cumbijín community, the majority of farms lack genealogy and production records, which makes it difficult to estimate the genetic merit of their animals. For this reason, the registry of 134 animals from 13 different farms was implemented, with information on each bovine through surveys and interviews with the producers, thanks to this, a database was created, on the subject of health, vitaminization, deworming, vaccination and gynecological check-ups. Production costs per liter of milk are in the range of 13 to 20 cents. and the sale price of a liter of milk is in a range of 40 to 42 cents. The approximate income from the sale of a liter of milk is acceptable since 61.54% of the farms obtain values greater than $450 and 38.46% values that exceed $1,000. Using the BLUP system, the genetic values of weight gain were estimated, which was low with an average of 57.69 gr/d. Like the density of the milk it was low (1.025 to 1.028 gr/ml). Finally, milk production is the main objective of improvement in the community since the response to the selection indicates that it could be increased to the next generation between 3847 and 4126 liters in a period of 305 days, which is a positive contribution since the average milk production is 3544.50 lt. technical records, balanced nutrition, infrastructure and animal identification must be implemented to increase the reliability of genetic evaluations